The psychological mechanism of basic psychological need frustration affecting job burnout: a qualitative study from China - Shi, Hairong (Frontiers in Psychology, 2024)
Job burnout is a common issue in nearly all professions, and it can have negative effects on employees, their families, clients, and organizations. It is important to address and resolve job burnout syndrome. Further research is needed to understand the underlying psychological mechanisms involved. This study introduces the concept of basic psychological need frustration to explore its impact on the psychological processes involved in job burnout.Methods: This study adopted a qualitative research methodology based on the principles of purposive sampling and convenience sampling. Eight grassroots senior counselors with more than 13 years of teaching experience at a Chinese university were selected as the study cases. The data were gathered through semistructured interviews and analyzed thoroughly via cluster analysis, which involved examining the text data word by word, sentence by sentence, line by line, and fragment by fragment. NVivo 11 software was used to register and code the text data.The study revealed that the subjects experienced high levels of frustration of their basic psychological needs. This frustration was evident in the coexistence of negative job characteristics and a lack of autonomy, a negative professional environment and a lack of competence, and the negative behavior of others and relationship frustration. The study also revealed that the four types of basic psychological need frustration were strongly linked to job burnout: a lack of control motivation or motivation, the pursuit of external goals, and negative behavior patterns, and the causal orientation of a controlled style. These factors positively predicted various dimensions of job burnout and positively affected the frustration of basic psychological needs.This study effectively explains the psychological process behind why individuals experience severe job burnout in a controlled organizational environment due to frustration of basic psychological needs. This study also highlights the internal causal relationship between basic psychological needs frustration and job burnout. This insight can help employees and organizations prevent and detect early job burnout syndrome and enhance employees' occupational well-being and organizational vitality.